Neurological Investigation and Treatment of Polioencephalomalacia affected goats - Arun George (Department of Clinical Medicine, College of Veterinary and Animal Sciences, 2000)
Seven goats diagnosed to be suffering from polioencephalomalacia were used for the present study. It included detailed clinical and neurological examination, CSF collection and analysis, electroencephalography, cranial radiography, histopathology of brain and assessment of the therapeutic efficacy of thiamine hydrochloride intravenously and bismuth carbonate orally in PEM cases. History of the affected animals suggested that feeding of rice gruel (a carbohydrate rich diet) could be one of the predisposing causes for the development of PEM of goats in Kerala. The characteristic clinical signs were head tilt, lateral deviation of head, nystagmus, circling, staggering gait, broad based stance and lying only on one side. Nervous system examination revealed depressed behaviour and deficits in posture and gait. Majority of the cranial nerves did not show deficits. Defects in postural reaction and abnormalities in spinal cord reflexes were detected. CSF examination revealed a significant increase in the mean total protein concentration and a non-significant increase in the total leucocyte